Fertilizing and Pruning Application for the Flowering and Fruiting of Conjoined Citrus - I Nyoman Sumerta; Ni Komang Alit Astiari; Luh Kartini (Warmadewa University Press, 2019)
This study aims to examine the application of fertilizing and pruning for the flowering and fruiting of conjoined citrus plants and their interactions. This study used a randomized-group design, arranged factorially with two factors, namely Fertilizing (F) and Pruning (P). The first factor that was experimented was fertilization (F) consisting of 3 levels, namely P0 (fertilization following the farmers' way only with manure), F1 (fertilizing with manure, N, P, K and Ca), F2 (fertilizing with manure N , P, K, Ca + Cu and Zn), while the second factor that was experimented was pruning (F) consisting of 3 levels, namely F0 (without pruning), F1 (young shoots trimmed), F2 (young shoots, twigs and leaves that were stricken with disease and were shaded, trimmed). Fertilizing and pruning treatments have a very significant effect on the number of fruits formed per tree. The results show that obtaining highest number of fruits formed per tree in fertilizing treatment with manure N, P, K, Ca + Cu and Zn was 256.00 pieces, increased by 95.79% compared with that of the lowest number in fertilizing treatment carried out only by manure, which was 130.75 pieces. The conclusion that obtained highest number of fruit per tree in the treatment of pruning the young shoots, twigs and leaves that were stricken with disease and were shaded was as many as 222.42 pieces, an increase of 25.71% compared with that of the lowest number in the treatment without pruning, which was only 176.92 fruit.